The Potential Use of some Plant-extracts against Coriolus Versicolor - Bhardwaj, S. K. (Indian Forester, 2009)
Aqueous extracts from twenty plants were tested for their antifungal activity against Coriolus versicolor inciting wood rot in trees. Test results showed a differential activity of the plant extracts against the mycelium growth. The maximum inhibitory effect was shown by stem extract of Aloe vera against the mycelium growth of test fungi. The root extracts of Asparagus racemosus, leaf extract of Azadirachta indica and leaf extracts of Camellia sinensis showed strong inhibitory effect against the test fungi. The flower extracts of Adhatoda vasica and seed extract of Albizia lebbek showed appreciable good inhibitory effect against the test fungi.